Cardiovascular Risk Factors and Distributions of the Ankle-Brachial Index among Type 2 Diabetes Mellitus Patients - Badaruddoza Doza; Manpreet Kaur; Sonia Chopra; Rohit Kapoor (International Journal of Hypertension)
Background. The aim of present study is to observe the association between the levels of ankle-brachial index (ABI) and cardiovascular risk factors among people with type 2 diabetes mellitus in north India. A cross-sectional study was carried out at a centre for heart and diabetic clinic in the state of Punjab on 1121 subjects (671 males and 450 females) with type 2 diabetes mellitus. History of symptoms related to cardiovascular diseases was noted, and blood pressure and anthropometric measurements were recorded. Ankle-brachial index (ABI) was measured using ultrasonic Doppler flow detector. Subjects with ABI ≤0.9 and ≥1.30 were classified as having low and high ABI, respectively. Females had a higher BMI and brachial-ankle pulse wave velocity (𝑃<0.001). Whereas, males had higher diastolic blood pressure and duration of type 2 diabetes mellitus. The differences of systolic blood pressure and ankle-brachial index were not found significant between the sexes. The prevalence of low ABI (<0.9) was 4.47% in men and 4.67% in women and high ABI (≥1.30) was prevalent in 14% of men and 10.45% of women. Age, BMI, baPWV, and blood pressures were significantly associated with ABI value in both sexes. The results suggested that the ABI might be used as a strong indicator for cardiovascular risk factors in type 2 diabetic subjects.